The Dynamics of Representing Nepal’s Struggle for Modernization: from Nepalization to Fatalism - KC, Gaurab; Kharel, Pranab (Dhaulagiri Journal of Sociology and Anthropology, 2017)
This article examines the popular as well as controversial work Fatalism and Development: Nepal’s Struggle for Modernization (1991) by anthropologist Dor Bahadur Bista. The authors historically chart out and evaluate the writing trajectory of Bista. The paper focuses on Bista’s consistent pitching for fatalism to be the root cause of underdevelopment in Nepali society starting with his writings in the 1960s, even though he may be using different terms to refer to the process. He pointed out certain groups close to the power structures including priestly Brahamins to be responsible for the underdevelopment and fatalism. His iconoclastic stance on the value system revolving around the power centers found many takers in the changed context of Nepal after 1990. This was furthered by his silence on the similar acts of other cultural groups. Dhaulagiri Journal of Sociology and Anthropology Vol.11, 201; 130-150